Interpretation Innovative Work Behavior and Transformational Leadership: Analysis Work Engagement and Work Environment on Dinas Pariwisata Kota Padang - Chintya Ones Charli; Ariyanto Masnum; Rahmadani Hidayat; Menhard Menhard; Budi Hartoyo (Journal of Accounting and Finance Management, 2023)
This research is aimed at uncovering the influence of Work Engagement and Work Environment on Innovative Work Behavior through Transformational Leadership as an Intervening variable. The research was conducted at the Padang City Tourism Office. The study population was 60 employees who worked in the Padang City Tourism Office, both civil servants and honorary employees. Furthermore, 60 employees became research samples taken proportionally and randomly with proportional random sampling techniques. Structural equation modeling (SEM) with a partial least square (PLS) approach is applied as a data analysis method. The results of the study revealed that work engagement and transformational leadership affect Innovative work behavior and work environment does not affect innovative work behavior. Work engagement affects transformational leadership, work environment does not affect transformational leadership. And there is an indirect influence between work engagement and innovative work behavior through transformational leadership.